Malignant Tumor of the Mandible – Secondary Leading to Primary: A Case Report with the Review of the Literature - Anuradha Yadav; Nandini Goswami; Roopika Handa; Surbhi Agarwal (Asian Pacific Journal of Cancer Care, 2023)
Metastatic adenocarcinoma of jaw-bone accounts for 1-3% and is commonly seen in the fifth and sixth decades. Most metastases of the oral cavity from primary locations have been described in the lungs, breasts, kidneys, and colon in adult patients. Oral Clinicians apart from diagnosing systemic diseases like diabetes, gastrointestinal disorders etc, could be the first ones to diagnose malignancies of different parts of the body before any oncologist and general physicians. Specialized imaging like PET/CT aids in diagnosing the primary tumor in such cases. To increase the survival time of such patients extensive mandibulectomy followed by other multimodal treatment options like palliative care should be considered. Here, in this paper, we aim to present a case of a young 24-year- old female with a metastatic tumor of the mandible that ultimately gave us the roadmap for diagnosing the primary tumor of the breast and also to review the literature of such cases.